German-Soviet Cooperation in the Arctic during the Weimar Republic: Friedrich Schmidt-Ott’s contribution - Lüdecke, Cornelia (Journal of Northern Studies, 2022)
Without Friedrich Schmidt-Ott, President of the Notgemeinschaft der Deutschen Wissenschaft/Emergency Association of German Science (today: Deutsche Forschungsgemeinschaft/German Science Foundation), and his good personal relations, favoured by the Treaty of Rapallo, German-Soviet-Russian cooperation in the Arctic would not have been conceivable in the early 1930s. It will be shown in this article how he helped to set up the International Study Association for the Exploration of the Arctic Region by Airship (in short: Aeroarctic), bringing researchers from Germany and the Soviet Union together again in an international research community while both countries were excluded from the International Research Council. The aim was to open up an Arctic transport route with airships. On the Soviet side, the polar researcher Rudolf Samoilovich played an important role in the preparation of the Arctic expedition of the LZ 127 Graf Zeppelin, which was planned by the Aeroarctic under Fridtjof Nansen and carried out after his death by Hugo Eckener together with the scientific director Samoilovich. In addition, Samoilovich facilitated the participation of German geophysicists in Soviet expeditions during the Second International Polar Year (1932–1933). Kurt Wölken carried out seismic ice thickness measurements on Novaya Zemlya, while Joachim Scholz determined air electricity and ultraviolet radiation on Franz Joseph Land and observed polar lights. In addition, both investigated sound propagation in the high atmosphere. Their different fates during the Third Reich are also revealed. It was not until 1998 that joint German-Russian research projects in the Arctic were resumed again.